Analysis of sensitive factors for sidetrack drilling in water-flooded oil reservoirs: data mining based on actual field data - Wang, Xiang; Rui, Cheng; Liu, Haicheng (Frontiers in Energy Research, 2023)
Sidetracking technology is an important measure to increase production and efficiency, too many complex factors affect the development effect of sidetracking wells. At present, most of the research on sensitive factors of sidetracking wells is based on theory, numerical simulation, or application analysis of limited wells. In this study, we adopt a data-driven research paradigm to conduct data mining studies on the actual data of a large number of sidetracking wells accumulated in the oil fields. Actual data from more than 130 sidetracking wells in oil fields within five years is collected and cleaned. An index system including 25 indicators for the analysis of sidetracking effect and a sample set of influencing factors are established. On this basis, scatter plots between various influencing factors and sidetracking development effect parameters are drawn to achieve intuitive qualitative understanding through visualization. The correlation coefficients between each parameter are calculated by Pearson and Spearman correlation analysis methods to quantitatively characterize and analyze the linear and nonlinear correlation degrees between each indicator. A feature importance calculation method based on a decision tree is constructed to calculate and rank the importance of each influencing factor for the development effect of sidetracking wells. The results show that compared with Pearson, the Spearman correlation coefficient can more accurately reflect the complex nonlinear correlation relationship between each indicator. Four indicators such as sidetracking target point position show medium or above correlation with sidetracking development effect. Through the calculation of the feature importance of the decision tree, it can be known that the importance of remaining recoverable reserves to the development effect of sidetracking wells exceeds 10%. The importance of six indicators, such as perforation thickness, is small, all less than 3%. This research work can provide guidance for future sidetracking well design and development work.